New Theoretical Framework Corporate Social Responsibility: The Case Of Islamic Development Bank’s Sustainable Social Program - Zaki Elden, Nail; Abdul Hamid, Mohd Syaiful Rizal Bin; Boon Cheong, Chew; Ali Al-Shami, Sayed Samer; Elzamly, Abdelrafe; Doheir, Mohamed (Opción, 2019)
The concern of this study is to propose theoretical framework for corporate social responsibility. Additionally, this paper also provides the suggestions to improve the role of IDB on incorporate social responsibility and sustainability. This research brought new evidence about the impact of social programme from IDB perspec- tive which is one of the first studies in this field. But this study stated that IDB develop standards for sustainable social programs which mix impact with positive, there is cooperation between all IDB’s related departments and cross departments committees to initiate, manage, monitor and evaluate sustainable social programs in coordinating with local government and local executing agent or NGOs; IDB’s departments know how to determine beneficiaries and the access to them through their local partners with standards and series of approvals for proposed projects and when the project complete will be transferred to local agency or government. Theoretical framework for corporate social responsibility includes corporate social responsibility, sponsors, social sustainable programs, charitable organizations & NGOs, social goals. The research is a single case study where the focus is only CSR in IDB and Abo-Halima Project. Other researchers who are interested about the research can opt to conduct the researches in other MDBs. Thus, this research developed the following objective to address this gap.